The impact of information technology on performance: The mediating role of management accounting system - Ismail, Noor Azizi (Universiti Teknologi Malaysia, 2007)
This paper reports the results of a study which offers an explanation for the relationship between Information Technology (IT) sophistication and performance of small and medium sized enterprises (SMEs), by incorporating into the model of the capability of management accounting systems to generate management accounting information (MAS capacity). To assess the relationship,data were collected from 310 (25% response rate) SMEs by way of questionnaire surveys. The results indicate that IT sophistication is a determinant of MAS capacity, which, in turn, is a determinant of firm performance. In other words, MAS capacity plays a mediating role in the relationship between IT sophistication and firm performance. An interpretation of the results is that those firms that employed sophisticated IT can generate sufficient management accounting information and thereby improve performance.